Strategi Pemerintah Republik Indonesia dalam Penanganan Masalah Pelintas Batas Indonesia-Timor Leste - Remigius Seran (Universitas Airlangga, 2018)
ABSTRACTThe urgency to set up the Border Between Indonesia and Timor-Leste and the border crossers is based on much more complex historical reasons than the arrangement of Indonesia's borders with other countries. Border governance policies between Indonesia and Timor-Leste are characterized by: border governance policies indicate a desire to adopt an integrated approach, governance practices tend to be fragmented where two very dominant approaches are the security approach and the socio-economic welfare approach. A border governance policy that ignores cultural identity variables leads to a reverse response, namely the use of cultural identity to challenge the country's dominant conception and policy in border governance. The phenomenon of